2020
DOI: 10.1101/2020.12.21.423514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Community Challenge for Pancancer Drug Mechanism of Action Inference from Perturbational Profile Data

Abstract: SUMMARYThe Columbia Cancer Target Discovery and Development (CTD2) Center has developed PANACEA (PANcancer Analysis of Chemical Entity Activity), a collection of dose-response curves and perturbational profiles for 400 clinical oncology drugs in cell lines selected to optimally represent 19 cancer subtypes. This resource, developed to study tumor-specific drug mechanism of action, was instrumental in hosting a DREAM Challenge to assess computational models for de novo drug polypharmacology prediction. Dose-res… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 63 publications
(83 reference statements)
0
28
0
Order By: Relevance
“…The single drug sensitivity is characterized as a dose-response curve with its IC50 and RI (relative inhibition) values. RI is the normalized area under the log 10 -transformed dose-response curves, which has shown enhanced robustness to characterize drug sensitivity ( 35 ). Moreover, RI can be interpreted as percentage inhibition, summarizing the overall drug inhibition effects relative to positive controls.…”
Section: Resultsmentioning
confidence: 99%
“…The single drug sensitivity is characterized as a dose-response curve with its IC50 and RI (relative inhibition) values. RI is the normalized area under the log 10 -transformed dose-response curves, which has shown enhanced robustness to characterize drug sensitivity ( 35 ). Moreover, RI can be interpreted as percentage inhibition, summarizing the overall drug inhibition effects relative to positive controls.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that drug MoA—as represented by differentially active proteins in response to the drug and measured by VIPER analysis of drug perturbation profiles in lineage-matched cells—is well recapitulated in vivo and in explants when the activity of their MR proteins is conserved(21, 32). Among the 25 cell lines for which perturbational profiles had been generated in the PANACEA database (PANcancer Analysis of Chemical Entity Activity)(33), 2 cell lines, LoVo and NCI-H1973, are the closest lineage-matched representative models of the GI epithelial and lung epithelial cells, respectively. However, while LoVo (human colon cell line) showed significant conservation of MR proteins with a colon adenocarcinoma cell line susceptible to SARS-CoV-2 infection (Caco-2(34), Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To facilitate the interpretation of mechanisms of action of drug combinations, it would therefore be beneficial to provide data integration tools for effective annotation and accurate matching to public databases such that more comprehensive features used for synergy predictions can be obtained. Efforts regarding annotating and harmonizing existing drug screening data, such as DrugComb 24,29 and DrugCombDB 30 , have significantly contributed to the development of data-driven pharmacological modelling [31][32][33] . For newly generated drug screening datasets, we have developed the SynergyFinder Plus portal further as a companion tool for retrieving publicly available information in a more automated fashion.…”
Section: Annotation Of Mechanisms Of Action Of Drug Combinationsmentioning
confidence: 99%